Menelusuri Kehidupan Penambang di Desa Sikalang: Dampak Bagi Kehidupan dan Keselamatan Masyarakat Sikalang - Marni, Linda; Hutasuhut, Mawadda Salsabila; Taufik, Muhammad Alvito; Viona, Aulia; Widrian, Oksa Bayu; Hidayati, Ilda (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to deeply examine the lives of miners in Sikalang Village, West Sumatra, and the impact of mining activities on the local community's social, economic, and safety conditions. Sikalang Village is widely known for its generational mining activities, which serve as the main livelihood. While providing significant economic benefits, these activities cause serious problems like occupational safety risks and environmental degradation, leading to barren land. The study employs a descriptive qualitative approach, utilizing in-depth interviews, field observation, and documentation study for data collection. The findings indicate that mining shapes social identity and remains the primary source of income, but former mining areas show high levels of damage, characterized by barren soil. The risk of accidents and the lack of personal protective equipment are major safety concerns. Environmental rehabilitation efforts through Community Service Programs (KKN), such as replanting flowers and greenery, demonstrate a positive impact, with the emergence of new vegetation and increased community awareness. In conclusion, further collaboration among the community, government, and academia is necessary to establish a safe and sustainable mining system in the future